Pearls and Pitfalls of Forearm Nailing: Current Concept Review - Nandyala, Sreeharsha; Shore, Benjamin; Hogue, Grant (Journal of the Pediatric Orthopaedic Society of North America, 2021)
Pediatric forearm fractures are one of the most common injuries that pediatric orthopaedic surgeons manage. Unstable fractures that have failed closed reduction and casting require surgical intervention in order to correct length, alignment, and rotation to optimize forearm range of motion and function. Flexible intramedullary nailing (FIN) is a powerful technique that has garnered widespread popularity and adaptation for this purpose. Surgeons must become familiar with the technical pearls and pitfalls associated with this technique in an effort to prevent complications.